Spatial distribution of canine zoonotic enteroparasites in Bahía Blanca, Argentina - la Sala, Luciano Francisco; Leiboff, Anastasia; Burgos, Julián; Costamagna, Sixto R. (Revista Argentina de Microbiología)
The objectives of this research were: (1) to determine the occurrence of zoonotic enteroparasites in dog feces from Bahía Blanca, Argentina; (2) to characterize the spatial distribution of the parasites found in association with the quality of life index (QLI) in neighborhoods of Bahía Blanca; and (3) to determine if the presence of a particular parasite genus in a stool sample was facilitated or impeded by the presence of other parasite genera. Samples of dog stools (n = 475) were collected between December 2012 and December 2013 in areas with varying QLI. The association between QLI values and the presence of parasites was analyzed using logistic regression. Overall enteroparasite occurrence was 36.6%. Parasitic forms found included nematode larvae, cysts of Blastocystis spp., Giardia spp., and oocysts of Cryptosporidium spp., and eggs of Ancylostoma caninum, Toxocara canis, cestodes and Trichuris spp. For certain enteroparasites, we detected significant associations between their occurrence and QLI. Feces collected in areas with medium and low QLI were 2.46 and 5.43 times more likely, respectively, to contain A. caninum than stools from the high-QLI area. Samples from areas with low QLI were 2.36 times more likely to contain Trichuris spp. than those from the high QLI area. Regarding protozoa, feces from areas with low QLI were 2.4 times more likely to be positive than those from areas with high QLI. We demonstrated that canine zoonotic parasites have a wide distribution in the study area, and that occurrence is higher in neighborhoods with lower QLI. Fil: la Sala, Luciano Francisco. Universidad Nacional del Sur. Departamento de Biologia, Bioquimica y Farmacia. Catedra de Parasitologia Clinica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Leiboff, Anastasia. Universidad Nacional del Sur. Departamento de Biologia, Bioquimica y Farmacia. Catedra de Parasitologia Clinica; Argentina Fil: Burgos, Julián. Marine Research Institute; Islandia Fil: Costamagna, Sixto R. ...